2009
DOI: 10.1111/j.1600-0838.2009.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Digit ratio (2D:4D) predicts sporting success among female fencers independent from physical, experience, and personality factors

Abstract: Research particularly focusing on male athletes and popular sports (running and soccer) suggests associations of lower (masculinized) second-to-fourth digit ratio (2D:4D), a putative marker of prenatal androgen action, with better sports performance. Studies focusing on women, non-mainstream sports, or controlling for covariates relevant for sporting success are still sparse. This study examined associations between 2D:4D and performance of both male and female athletes active in fencing (a non-mainstream spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 28 publications
2
25
0
5
Order By: Relevance
“…It is also possible that many of the females who enter college coaching-many of whom were successful participants in sport themselves-subscribe to a traditionally masculine sport ethos of risk taking that closely resembles that of male coaches of male teams. To the extent that this is true, it may be a result of genetic or early life influences [65] or it may be the result of socialization over the course of their own athletic careers [66,67]. Little research to date has looked explicitly at the attitudes about toughness and playing through injury of female coaches.…”
Section: Discussionmentioning
confidence: 94%
“…It is also possible that many of the females who enter college coaching-many of whom were successful participants in sport themselves-subscribe to a traditionally masculine sport ethos of risk taking that closely resembles that of male coaches of male teams. To the extent that this is true, it may be a result of genetic or early life influences [65] or it may be the result of socialization over the course of their own athletic careers [66,67]. Little research to date has looked explicitly at the attitudes about toughness and playing through injury of female coaches.…”
Section: Discussionmentioning
confidence: 94%
“…Another reported that 2D:4D ratio in females was negatively correlated with the level achieved in sport participation (Paul, Kato, Hunkin, Vivekanandan, & Spector, 2006). A third study found that the 2D:4D ratio of elite fencers was negatively correlated with national rankings in females, but not in males (Voracek, Reimer, & Dressler, 2010). A fourth study examining this relationship in 72 females found no significant differences in 2D:4D ratios between athletes and controls (Latourelle, Elwess, & Elwess, 2008).…”
Section: Introductionmentioning
confidence: 90%
“…In populations varying from female fencers (Voracek et al 2010) to male sumo wrestlers (Tamiya et al 2011), individuals with lower digit ratios tend to be more successful. The information on non-human vertebrates is much scarcer and less consistent.…”
Section: Introductionmentioning
confidence: 98%